Serum adiponectin, leptin, resistin and RBP4 levels in obese and metabolic syndrome children with nonalcoholic fatty liver disease. (October 2013) - Boyraz, Mehmet; Cekmez, Ferhat; Karaoglu, Abdulbaki; Cinaz, Peyami; Durak, Mustafa; Bideci, Aysun
Aim: To investigate the relationship of adiponectin, leptin, resistin and RBP4 levels in obese and metabolic syndrome children with nonalcoholic fatty liver disease (NAFLD).Patients & methods: Group I consisted of 63 obese children with liver steatosis, group II consisted of 12 obese children with elevated serum ALT activity from group I, and group III included 85 obese children without liver steatosis.Results: Leptin levels were higher in the NAFLD children than in the control group. Serum RBP4 levels in obese children with NAFLD were higher than those in obese children without NAFLD and controls. Adiponectin and resistin levels were negatively correlated and RBP4 levels positively correlated with ALT activity and ultrasonographic grading.Conclusion: These data suggest that adiponectin, resistin and RBP4 may have a role in the pathogenesis of NAFLD in obese children. Adiponectin, leptin, resistin and RBP4 may be suitable markers for predicting metabolic syndrome and NAFLD.